Edukasi Pencegahan Pernikahan Dini Berbasis Sekolah: Strategi Intervensi dalam Menekan Risiko Stunting dan Putus Sekolah di Wilayah Desa Samangki - Muhammad Agung Pratama Anwar; Yusran Yusran (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
Early marriage remains a social problem that impacts the education, health, and future of the younger generation. A lack of understanding among adolescents and the community about the risks of early marriage is a major contributing factor to this practice. This community service activity aims to increase the knowledge and awareness of students and young people regarding the negative impacts of early marriage and the importance of planning for a healthy and sustainable future. The activity took place on January 12 at MA Darul Rasyidin, Samangki Village, Simbang District, Maros Regency. Methods used included outreach, discussion, and an interactive approach that actively engaged participants. The results of the activity showed an increase in participants' understanding of the risks of early marriage from a health, educational, social, and legal perspective. This activity is expected to be a preventative measure to reduce the number of early marriages and encourage the formation of a younger generation that is better prepared for the future.